1998
DOI: 10.1111/j.1469-7793.1998.243by.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Na+‐H+ exchange to sodium reabsorption in the loop of Henle: a microperfusion study in rats

Abstract: 1. The contribution of apical Na¤-H¤ exchange to sodium reabsorption in the thick ascending limb of the loop of Henle (TALH) in vivo was examined in anaesthetized rats by perfusing loops of Henle of superficial nephrons with solutions containing the Na¤-H¤ exchange inhibitor, ethyl isopropyl amiloride (EIPA). 2. Using a standard perfusate, no statistically significant effect of EIPA on net sodium reabsorption (JNa) was detected. However, when sodium reabsorption in the pars recta of the proximal tubule was min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…NKCC2-mediated Na ϩ reabsorption generates a lumen-positive PD TE , partly due to apical recycling of K ϩ . The Na ϩ /H ϩ exchanger also contributes to the apical Na ϩ entry, but the role is relatively minor and it does not generate lumen-positive PD TE (23). Several pieces of evidence indicate that the effect of KS-WNK1 on Na ϩ reabsorption in cTAL is at least in large part through inhibition of NKCC2.…”
Section: Discussionmentioning
confidence: 97%
“…NKCC2-mediated Na ϩ reabsorption generates a lumen-positive PD TE , partly due to apical recycling of K ϩ . The Na ϩ /H ϩ exchanger also contributes to the apical Na ϩ entry, but the role is relatively minor and it does not generate lumen-positive PD TE (23). Several pieces of evidence indicate that the effect of KS-WNK1 on Na ϩ reabsorption in cTAL is at least in large part through inhibition of NKCC2.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the use of this perfusate almost abolishes fluid reabsorption by the perfused loop [15,17]. It has been shown that the use of this perfusate almost abolishes fluid reabsorption by the perfused loop [15,17].…”
Section: Methodsmentioning
confidence: 97%
“…The use of the low-Na + perfusate in the present study has allowed us to gauge the full extent of the barium-induced reduction in Na + reabsorption in the TALH per se. We found that when barium was present the residual Na + reabsorption (149 ± 23 pmol min _1 ) was little greater than that attributable to luminal Na + -H + exchange (Shirley et al 1998b). However, even under these conditions, neither net K + reabsorption nor the concentration of K + in the collectate was significantly reduced.…”
Section: Discussionmentioning
confidence: 65%
“…It has been shown by Peterson et al (1993) and confirmed by us (Shirley et al 1998b) that the use of this perfusate almost abolishes fluid reabsorption (J V ) in the perfused loop, the residual J V being attributable to water reabsorption in the thin descending limb of Henle. Both groups have also shown that the addition of loop diuretics to the perfusate (thus blocking…”
Section: Low-na + Perfusatementioning
confidence: 70%
See 1 more Smart Citation